Progress in breeding maize for Striga tolerance/resistance at IITA - Kim, S.K.; Winslow, M.D. (1991)
IITA has been breeding maize for Striga tolerance/resistance (STR) since 1982. Populations of Striga hermonthica from Nigeria have been used to challenge maize germplasm. Initially (1982-1984), field screening was done under natural infestation, but variability both within sites and across years was high. Since 1985, fields have been infested artificially. Artificial infestations have been improved with experience, and variability has now declined to an acceptable level. The most important improvements were: a) lowering the nitrogen dose to 60 kg: b) infesting with very high rates of Striga seed, approximately 20,000 germinable seeds per square meter, and c) growing the crop on ridges 30 cm high. Antother bottleneck was the limitation of one crop per year under rainfed conditions. Since 1988, irrigated screenhouses have been used to screen limited amounts of key germplasm year-round. A number of hybrid varieties and open-pollinated populations have been identified which show moderate STR